A review on the effect of fabric reinforcement on strength enhancement of natural fiber composites - Arumugam, Soundhar; Kandasamy, Jayakrishna; Venkatesan, Subramani; Murugan, Rajesh; Narayanan, Valayapathy Lakshmi; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani; Md Shah, Ain Umaira; Khan, Tabrej; Sebaey, Tamer Ali (MDPI AG, 2022)
The main objective of this study is to examine the impact of reinforcements on the strength of natural fiber composites. Recent advancements in natural fiber composites have minimized the usage of man-made fibers, especially in the field of structural applications such as aircraft stiffeners and rotor blades. However, large variations in the strength and modulus of natural fiber degrade the properties of the composites and lower the safety level of the structures under dynamic load. Without compromising the safety of the composite structure, it is significant to enrich the strength and modulus of natural fiber reinforcement for real-time applications. The strength and durability of natural fiber can be enriched by reinforcing natural fiber. The reinforcement effect on natural fiber in their woven, braided, and knit forms enhances their structural properties. It improves the properties of natural fiber composites related to reinforcement with short and random-orientation fibers. The article also reviews the effect of the hybridization of natural fiber with cellulosic fiber, synthetic fiber, and intra-ply hybridization on its mechanical properties, dynamic mechanical properties, and free vibration characteristics, which are important for predicting the life and performance of natural fiber composites for weight-sensitive applications under dynamic load.